2020
DOI: 10.1017/ice.2020.189
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in trajectories of healthcare worker infections during the COVID-19 pandemic in Italy

Abstract: To the Editor-Healthcare workers (HCWs) have been key in the current global response against the COVID-19 epidemic; their safety can help address the clinical and public health challenges associated with SARS-CoV-2 infection. 1 As of late March, infections of HCWs in Italy reached a peak of 10.0% of the total COVID-19 cases, 2 representing a potential amplifier of the epidemic following the viral transmission within and outside the health facility environment, to HCWs, visitors, inpatients, and outpatients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
1
4
0
1
Order By: Relevance
“…This is in contrast with studies performed in Wuhan at the beginning of the epidemic which showed a higher risk of infection in low-risk units, where workers were less trained on the use of PPE [ 6 , 21 ]. Conversely, more recent Italian [ 22 24 ] and American studies [ 25 ] showed results similar to ours, alongside the Denmark study on seroprevalence (thus identifying also asymptomatic cases) that demonstrated a higher prevalence for workers in COVID-19 units than other frontline workers [ 26 ]. Besides, another retrospective survey conducted in our hospital found no correlation between working in COVID units and positive serostatus, presumably due to a higher risk awareness [ 27 ].…”
Section: Discussionsupporting
confidence: 85%
“…This is in contrast with studies performed in Wuhan at the beginning of the epidemic which showed a higher risk of infection in low-risk units, where workers were less trained on the use of PPE [ 6 , 21 ]. Conversely, more recent Italian [ 22 24 ] and American studies [ 25 ] showed results similar to ours, alongside the Denmark study on seroprevalence (thus identifying also asymptomatic cases) that demonstrated a higher prevalence for workers in COVID-19 units than other frontline workers [ 26 ]. Besides, another retrospective survey conducted in our hospital found no correlation between working in COVID units and positive serostatus, presumably due to a higher risk awareness [ 27 ].…”
Section: Discussionsupporting
confidence: 85%
“…The burden of COVID-19 among healthcare workers has been enormous during the ongoing COVID-19 pandemic [ [1] , [2] , [3] , [4] , [5] ]. Environmental sampling has demonstrated the presence of SARS-CoV-2, the causative agent of COVID-19, in indoor air and on various surfaces in healthcare settings [ [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%
“…The shortage of nurses and medical doctors front lining the emergency response, also in light of the high number of nurses and medical professionals testing positive to COVID-19 (Bellizzi et al ., 2020 ), forced the Government to introduce several measures (DL, 2020a , 2020b ; DPCM, 2020b ) in order to face the rapidly rising demand of extra medical and other health care personnel. These measures included inter-regional redistribution of health care personnel, the re-hiring of retired medics, nurses and other health care professionals, the creation of faster recruitment tracks, the possibility to employ personnel on a freelance basis, the hiring of 20,000 health care professionals (3.5% growth in the health workforce): the new hires comprised of more than 4300 additional medical doctors, mainly anaesthesiologists; around 9700 nurses; and 6000 other health care professionals, mainly technical personnel (Aimone Gigio et al ., 2020 ).…”
Section: Supply and Demand Side Considerations Of The Covid-19 Responmentioning
confidence: 99%